Enhancing Arabic Vocabulary Learning in Grade VIII Students through Interactive Quizzing: Meningkatkan Pembelajaran Kosakata Bahasa Arab pada Siswa Kelas VIII melalui Kuis Interaktif - Arrahma, Safinah Zahroh; Ammar, Farikh Marzuki (Indonesian Journal of Education Methods Development, 2023)
This study employs the R&D-ADDIE method to develop an innovative Arabic textbook, Al-'Ashri, utilizing the Quizizz platform for Grade VIII students at SMP Muhammadiyah 5 Tulangan. Addressing challenges identified by Arabic subject teachers—vocabulary retention difficulties and waning student interest—the research introduces interactive digital learning to replace conventional monotonous textbooks. Through interviews and expert validation, the study gauges enhanced engagement and improved vocabulary memorization facilitated by Quizizz. Survey responses from students highlight the platform's efficacy, shedding light on its potential to transform Arabic language education by fostering greater ease and enjoyment in the learning process. Highlights: Innovative Pedagogy: Development of an interactive Arabic textbook, Al-'Ashri, using Quizizz, addressing conventional learning challenges. Enhanced Engagement: Integration of Quizizz leads to increased student interest and active participation in Arabic language learning. Effective Vocabulary Retention: Research demonstrates improved vocabulary memorization through the interactive and engaging Quizizz platform. Keywords: Arabic vocabulary learning, interactive digital textbook, Quizizz, student engagement, vocabulary retention